2020
DOI: 10.29261/pakvetj/2019.128
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Experiments Revealed the Anthelmintic Potential of Herbal Complex against Haemonchus contortus

Abstract: In an era of drug resistance, new medicinal plants are being evaluated for control of parasites. In the present study, the anthelmintic activity of the extract of herbal complex (HC) composed of four herbs (Origanum vulgare, Cinnamomum verum, Rosmarinus officinalis and Capsicum annuum) was assessed against eggs and adult Haemonchus (H.) contortus. Egg hatch test (EHT) and adult motility assay (AMA) was performed to evaluate the anthelmintic potential of HC. The reference drug used in EHT was oxfendazole and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…This study's findings are similar to those of Ferreira et al [21], who reported that the leaf extract of Annona muricata L. could completely inhibit the motility of adult H. contortus worms in the first 6-8 h. Ahmed et al [22] stated that Artemisia herba-alba and Punica granatum had a significant effect on the mortality rate of adult H. contortus after 7 h of exposure. Zaman et al [23] reported that herbal complex extracts could cause 100% death in adult H. contortus worms 8 h post-exposure. Widiarso et al [24] Different superscripts indicate significant differences (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This study's findings are similar to those of Ferreira et al [21], who reported that the leaf extract of Annona muricata L. could completely inhibit the motility of adult H. contortus worms in the first 6-8 h. Ahmed et al [22] stated that Artemisia herba-alba and Punica granatum had a significant effect on the mortality rate of adult H. contortus after 7 h of exposure. Zaman et al [23] reported that herbal complex extracts could cause 100% death in adult H. contortus worms 8 h post-exposure. Widiarso et al [24] Different superscripts indicate significant differences (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…These plant products are mostly extracted from flowers and leaves of various aromatic plants growing in temperate and warm regions such as the Mediterranean, the Amazon or tropical countries, where they represent an important part of traditional pharmacopoeia (Bakkali 2008). The medicinal properties of EOs are recognized since ancient times which include antiviral, antibacterial, antifungal, antiparasitic, anti-inflammatory, antiseptic, anticancer and antispasmodic properties among others (Bakkali 2008;Mancianti and Ebani 2020;Zaman et al 2020). In veterinary medicine, EOs are increasingly used for the prevention and treatment of various animal diseases.…”
Section: Properties and Chemical Composition Of Essential Oilsmentioning
confidence: 99%
“…In recent years, botanical anthelmintics have emerged as an promising alternative in the control of ruminant GINs and as a tool to combat AR [8,[14][15][16][17]. Among other plant products, essential oils (EOs) are the most commonly mentioned and examined within that context [18].…”
Section: Introductionmentioning
confidence: 99%
“…These natural products have a long history of medical application in humans and are often utilized in many medical practices around the world. The medicinal properties of EOs include anti-inflammatory, antiseptic, anticancer, antispasmodic (and other positive impacts on the gastrointestinal tract), and even anti-anxiety properties, along with antibacterial, antifungal and antiparasitic effects [17,[20][21][22][23]. In veterinary medicine, EOs are increasingly used for the treatment and prevention of various diseases, but are still preferable in monogastric animals such as pigs and poultry [22,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%